Dose-dependent transitions in Nrf2-mediated adaptive response and related stress responses to hypochlorous acid in mouse macrophages - Woods, Courtney G. (2009)
Hypochlorous acid (HOCl) is potentially an important source of cellular oxidative stress. Human HOCl exposure can occur from chlorine gas inhalation or from endogenous sources of HOCl, such as respiratory burst by phagocytes. Transcription factor Nrf2 is a key regulator of cellular redox status and serves as a primary source of defense against oxidative stress. We recently demonstrated that HOCl activates Nrf2-mediated antioxidant response in cultured mouse macrophages in a biphasic manner. In an effort to determine whether Nrf2 pathways overlap with other stress pathways, gene expression profiling was performed in RAW 264.7 macrophages exposed to HOCl using whole genome mouse microarrays. Benchmark dose (BMD) analysis on gene expression data revealed that Nrf2-mediated antioxidant response and protein ubiquitination were the most sensitive biological pathways that were activated in response to low concentrations of HOCl (< 0.35 mM). Genes involved in chromatin architecture maintenance and DNA-dependent transcription were also sensitive to very low doses. Moderate concentrations of HOCl (0.35 to 1.4 mM) caused maximal activation of the Nrf2-pathway and innate immune response genes, such as IL-1β, IL-6, IL-10 and chemokines. At even higher concentrations of HOCl (2.8 to 3.5 mM) there was a loss of Nrf2-target gene expression with increased expression of numerous heat shock and histone cluster genes, AP-1-family genes, cFos and Fra1 and DNA damage-inducible Gadd45 genes. These findings confirm an Nrf2-centric mechanism of action of HOCl in mouse macrophages and provide evidence of interactions between Nrf2, inflammatory, and other stress pathways.